Develop Students Literacy and Creativity Efforts at SDN 4 Wates Through the Making of Wall Magazines: Upaya Pengembangan Literasi dan Daya Cipta Peserta Didik di SDN 4 Wates Melalui Pembuatan Mading - Diyah Ayu Saputri; Densi Himelda Yusvita Dewi; Mohammad Firza Renaldi; Nabila Mahari Pramesti; Tariza Lailinikmah; Adinda Merinisa Septirian (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Literacy and creativity are important skills in education that can support students' ability to read, write, and develop innovative ideas and concepts. Based on UNESCO data in 2017, Indonesian students are still considered to have poor reading skills. Mading or wall magazines are one way to improve students' literacy and creativity. Mading can be a means of expression for students to channel ideas and practice their writing skills. SDN 4 Wates, Tulungagung Regency is the location of community service activities that aim to improve students' writing skills through the creation of class mading. Students in grades 5 and 6 receive training and mentoring through a descriptive qualitative approach. This activity involves several stages, namely analysis of school conditions, preparation of materials and tools, implementation of making mading, and evaluation of the effectiveness of the program. The results of this activity show that students are more motivated to write and express their ideas creatively, and there is an increase in active participation in literacy activities at school. Thus, the use of mading as a learning medium has proven effective in encouraging a culture of literacy and student creativity.